2008
DOI: 10.1162/jocn.2008.20061
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Perceived Direction of Motion Caused by Spatial Undersampling in Two Children with Periventricular Leukomalacia

Abstract: Abstract& We report here two cases of two young diplegic patients with cystic periventricular leukomalacia who systematically, and with high sensitivity, perceive translational motion of a random-dot display in the opposite direction. The apparent inversion was specific for translation motion: Rotation and expansion motion were perceived correctly, with normal sensitivity. It was also specific for random-dot patterns, not occurring with gratings. For the one patient that we were able to test extensively, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Timing of arrival of spike input to cortex is crucial for motion perception. Jitter in temporal delay of the order of milliseconds is sufficient to disrupt or even invert motion [ 77 ]; disorganization of input spike trains or high levels of noise may be sufficient to impede the formation of direction selectivity at the cortical level. As input motion signals become more reliable and organized, the cortex may be capable of developing the complex neuronal circuitry for direction selectivity and trajectory integration only within a very limited time window.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of arrival of spike input to cortex is crucial for motion perception. Jitter in temporal delay of the order of milliseconds is sufficient to disrupt or even invert motion [ 77 ]; disorganization of input spike trains or high levels of noise may be sufficient to impede the formation of direction selectivity at the cortical level. As input motion signals become more reliable and organized, the cortex may be capable of developing the complex neuronal circuitry for direction selectivity and trajectory integration only within a very limited time window.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired motion perception is common in children born before 34 weeks, and is more marked in those who manifest periventricular white matter lesions (Guzzetta et al 2009 ). Specifi c aspects of motion perception can be defi cient, for example the perception of linear motion, while other aspects, such as seeing radial and circular motion may be intact in children with evidence of periventricular white matter pathology ( Morrone et al 2008). Children born extremely prematurely may also have diffi culties with motion-defi ned form processing, but may in addition exhibit problems with visual search, stereopsis, and with visuo-spatial tasks (construction, mental rotation) (Jacobson et al 2006 ).…”
Section: Perception Of Movementmentioning
confidence: 99%
“…The authors suggested that there may therefore be different developmental requirements for establishment of different neural processes (such as the requirement of precise timing of neural signals) rather than differential vulnerability of different anatomical regions and proposed that extrastriate mechanisms develop in parallel but the dorsal stream has a greater vulnerability to early neurological impairment. Recent work by Morrone et al [78] reported two cases of diplegic children with PVL who both perceived translational motion of a random-dot display in the opposite direction. Circular and radial motion perception was normal, reinforcing the idea that translational motion is processed in a separate area.…”
Section: Ii) Dorsal Stream Dysfunction In Children With Cerebral Palsymentioning
confidence: 99%